DETERMINANTS OF MANDATORY E-BUPOT 21/26 CORETAX SYSTEM SUCCESS - Yudithia Mega Gumilang; Siti Mutmainah (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2026)
The implementation of integrated digital tax administration systems is a key strategy for improving public service quality and tax compliance in Indonesia. As part of this reform, the electronic tax deduction receipt (e-Bupot) 21/26 has been integrated into the Coretax platform and is mandatory for taxpayers. Despite its strategic role, the early implementation of this system has revealed several challenges related to system performance, information reliability, and the availability of user support services, raising concerns about its actual success from the user’s perspective. This study evaluates the success of the e-Bupot 21/26 by applying the DeLone and McLean Information System Success Model in a mandatory use context. The analysis focuses on system quality, information quality, service quality, user satisfaction, and perceived net benefits. Using a quantitative survey, primary data were collected from users who actively use the system for tax withholding and reporting. The findings indicate that system success in a mandatory environment is not determined solely by technical performance but is strongly influenced by reliable information and responsive service support, which enhance user satisfaction and perceived benefits.